A pediatric case of dupilumab-induced pustular psoriasis - Nan Dang; Huiwen Zheng; Yunqing Ren (Taylor & Francis Group, 2024)
Aim: Dupilumab is a novel treatment agent for moderate to severe atopic dermatitis (AD) with few adverse effects. Drug-induced psoriasiform lesions are rare.Methods: We report a 4-year-old boy with AD who developed pustular psoriasis during treatment with dupilumab.Results: Pustular psoriasis appeared within 1 week of treatment and worsened in the second week. After stopping dupilumab administration, topical corticosteroids (desonide and mometasone furoate creams) and oral desloratadine without relief. Pustular psoriasis was confirmed by pathological examination, and thiamphenicol was administered. After 2 weeks of treatment, the lesions nearly resolved without recurrence in 1-year follow-up.Conclusions: Dupilumab-induced pustular psoriasis is rare in children.